Kemampuan Kitinase Streptomyces RKt5 sebagai Antijamur terhadap Patogen Fusarium oxysporum - Yurnaliza, Yurnaliza; Margino, Sebastian; Sembiring, Langkah (Jurnal Natur Indonesia, 2011)
The purpose of the reasearch is to determine of antifungal activity from chitinase from Streptomyces RKt5 to inhibite growth of Fusariumoxysporum. The chitinase of Streptomyces RKt5 produced in liquid chitin medium with optimum conditions (inoculum concentration, pHand incubation time) and then partially purified with ammonium sulphate. The enzyme products were tested the antifungal activity againstF.oxysporum. The results showed that mycelial growth of F.oxysporum can be inhibited by Streptomyces RKt 5 in dual culture test. Thepartial purified chitinase enzyme couldn’t inhibit the fungal growth. But if the mycellium fragmented, the enzyme could degrade the fungalcell wall in incubation time. The frequency of fungal cell wall lysis and levels of N-acetylglucosamine released that have been increasingalong with the length of incubation time.